Flip and Flop - Apperley, Dawn. (New York : Scholastic, 2001)
A two-year-old penguin named Flop is sad when his five-year-old brother, Flip, would rather play with a friend his own age.
Keywords: Brothers -- Fiction; Penguins -- Fiction; Play -- Fiction; Penguins -- Juvenile literature